Management Of Assembly Taklim Al-Hikmah Management In Increasing Residents’ Interest In Following Resurrections In Kebun Bunga Village, Sukarami Sub-District, Palembang City - Tripina Anamiah, Alrama; Nuraida, Nuraida; Walian, Anang (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
The thesis entitled "Management of the Al-Hikmah Taklim Assembly in Increasing Residents’ Interest in Participating in Recitations in Kelurahan Kebun Bunga, Sukarami District, Palembang City". With the formulation of the problem, namely (1) how is the management of the Al-Hikmah Al-Hikmah Kelurahan Kebun Bunga management? And (2) what are the efforts of the Al-Hikmah taklim assembly in cultivating the interest of Kebun Bunga kelurahan residents so they are interested in joining the taklim assembly? The type of writing used is qualitative writing. Data collection techniques include observation, interviews and documentation. The theory used is Georry Terry’s theory for management and Crow and crow theory as the interest of the assembly. The results of writing (1) management that is applied in the Taklim Assembly is appropriate and effective through planning, organizing, actualting and controlling. Through the stages of controlling (supervision) it can be formulated as a process of determining what must be achieved, what will be done, namely implementation, assessing implementation and if necessary making improvements, so that implementation is according to plan. (2) An increase in one’s religious understanding can be seen from how much the religious dimension is applied in human life, this is in line with the Crow and Crow theory, where the emergence of motivation in a person is asking for a tendency to manifest oneself who has potential and understands one’s own desires first. don’t follow takliman yourself not at the will of the congregation.